A hybrid indirect matrix converter immune to unbalanced voltage supply, with reduced switching losses and improved voltage transfer ratio - Klumpner, Christian (2005)
Achieving a compact and efficient design of power electronic converters is not a straightforward procedure: minimizing the size of the filter requires a higher switching frequency that causes additional switching losses that will require a larger heatsink and therefore will increase the equipment size. A matrix converter (MC) is known to have smaller switching losses than a Voltage Source Inverter (VSI) and therefore a greater potential for size reduction but has higher conduction losses. A two-stage Indirect MC (IMC) behaves similar to a MC but its losses follow a profile similar to a VSI. The two-stage hybrid IMC which is the latest development, offers a significant improvement in the voltage transfer ratio and immunity against unbalanced voltage supply but due to the additional intermediary stage, has even higher conduction losses than indirect MCs. This paper proposes a new control strategy for a hybrid IMC that will improve both the voltage transfer ratio and the efficiency of the converter at maximum output voltage by modulating the DC-link voltage across the inverter stage in order to eliminate the zero-voltage states and their corresponding commutations.